Flap necrosis after palatoplasty in irradiated patient and its reconstruction with tunnelized-facial artery myomucosal island flap - Hye-In Jeong; Hye-Min Cho; Jongyeol Park; Yong Hoon Cha; Hyung Jun Kim; Woong Nam (SpringerOpen, 2017)
Abstract Background Tunneled transposition of the facial artery myomucosal (FAMM) island flap on the lingual side of the mandible has been reported for intraoral as well as oropharyngeal reconstruction. This modified technique overcomes the limitations of short range and dentition and further confirms the flexibility of the flap. This paper presents a case of reconstructing secondary soft palatal defect due to flap necrosis following two-flap palatoplasty in irradiated patient with lingually transposed facial artery myomucosal island flap. Case presentation The authors successfully reconstructed secondary soft palatal defect due to flap necrosis following two-flap palatoplasty in an irradiated 59-year-old female patient with tunnelized-facial artery myomucosal island flap (t-FAMMIF). Conclusions Islanding and tunneling modification extends the versatility of the FAMM flap in the reconstruction of soft palatal defects post tumor excision and even after radiation, giving a great range of rotation and eliminating the need for revision in a second stage procedure. The authors thus highly recommend this versatile flap for the reconstruction of small and medium-sized oral defects.